Менеджмент в сфері регіонального туризму: сучасний стан та перспективи - Перерва, Петро Григорович; Кармінська-Бєлоброва, Марина Володимирівна; Проскурня, Олена Михайлівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
У статті наведені основні напрями та перспективи державної регіональної політики у сфері туризму: подолання відсталості регіону за рахунок розробки регіональних програм; створення засобів суб'єктів господарювання; збереження єдиного економічного простору і загальних принципів функціонування структур туристичного бізнесу на всій території України; залучення громадськості та різних служб міст і районів регіону до процесу планування туризму; розвиток туристично-екскурсійної активності населення, освоєння туристських територій, відновлення і пристосування пам'яток історії, культури, архітектури, природи для цілей туризму, екскурсій і відпочинку; допомога в подоланні відмінностей в рівні життя населення окремих регіонів; організація і управління економікою туристського комплексу на основі кооперації громадських державних організацій і особистих можливостей громадян.

The article discusses the management of regional tourism, which is one of the promising areas of activity. Its significance lies in the fact that, firstly, it is the sphere of rapid capital turnover with relatively small capital investments; secondly, it is an effective means of modernizing infrastructure and, thirdly, the possibility of creating new jobs both in the state and in the regional economy. Recently, favorable conditions have been created for entrepreneurship and the development of tourist and recreational regions, the improvement and promotion of national culture. The tourism business acquires particular relevance in connection with the dismissal of labor resources, which can find application in the tourism industry. With the help of management, a development strategy should be developed, both for the entire region and for a separate tourism organization. It is proposed to develop an effective strategy for the development of a tourist region, it is advisable to structure the tourist region in accordance with the allocated consumer values of tourists into smaller hierarchical levels. The article presents the main directions and prospects of the state regional policy in the field of tourism: overcoming the backwardness of the region through the development of regional programs; creation of funds of business entities; preservation of a single economic space and general principles of functioning of tourist business structures throughout Ukraine; involvement of the public and various services of cities and regions of the region in the tourism planning process; development of tourist and excursion activity of the population, development of tourist territories, restoration and adaptation of monuments of history, culture, architecture, nature for the purposes of tourism, excursions and recreation; assistance in overcoming differences in the standard of living of the population of certain regions; organization and management of the economy of the tourist complex on the basis of cooperation of public state organizations and personal capabilities of citizens.
Regional tourism management: current state and prospects
Keywords: менеджмент; туристична діяльність; регіональна політики; туризм; стратегія розвитку; management; tourism activity; regional policy; tourism; development strategy